Racing Fast and Slow: Defining the Tactical Behavior That Differentiates Medalists in Elite Men's 1,500 m Championship Racing - Sandford, Gareth N.; Day, Benjamin T.; Rogers, Simon A. (Frontiers in Sports and Active Living, 2019)
Background: 1500m running has long been a blue ribbon event of track championship racing. The eventual medalists employ common tactical behaviors such as a fast sustained pace from the start (gun-to-tape), or, slow initial laps that precede a precisely timed race kick. Before the kick, there are positional changes caused by surging, that can go uncharacterized. The inter-relationship of surge events, tactical positioning and kick execution may have important implications for eventual medal winning outcomes and require further definition. Methods: In a randomized order, three middle-distance running experts were provided publically available video (YouTube) of sixteen men’s 1500m championship races across, European, World and Olympic championships. Each expert determined the occurrence of surges (defined as any point in the 1500m after the first 300m where an athlete repositions by ≥3 places; or noticeably dictates a raise in the pace from the front) and the race kick. Following a second level verification of expert observations, tactical behaviors (quantity and distance marker within each race) mean distance from the finish were compared between fast (≤3:34.00, n=5), medium (>3:34.00 - ≤3:41.99, n=7) and slow (≥3:42.00, n=4) race categories. Results: Before the race kick, there were more surges in slow (5±1.7, mean ±90% confidence limits) versus fast races (1±0.4, very large difference, very likely). The final surge before the race kick occurred earlier in fast (704±133m from the finish) versus medium (427±83m, large difference, most likely), and slow races (370±137m, large difference, most likely). At initiation of the race kick in fast races, large positional differences were found between eventual gold (2±1.2; likely) and silver (2.2±1.6; likely) versus bronze medalists (4.4±1.2). In slow races, positional differences were unclear between eventual gold (4.3±4.7), silver (4.8±4.8) and bronze medalists (5.3±1.5). Regardless of category, the race kick occurred on the last lap, with unclear differences between fast 244±92m medium 243±56m and slow 236±142m races. Conclusions: Presenting tactical behaviours by race categorization (slow, medium , fast race times), provides a novel understanding of the nuance of racing tactics. The present findings highlight the importance of considering within race athlete decision making across multiple-race scenarios during championship preparation.